2018
DOI: 10.1002/oa.2695
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the association between subsistence strategies and the timing of weaning among indigenous archaeological populations of the Caribbean

Abstract: Human breastfeeding is a biocultural process shaped by the interaction of numerous biological, cultural, economic, and social factors. Although previous studies have found that a society's subsistence economy alone does not determine weaning timing, subsistence may still have a profound effect on weaning food choices. This paper analyses nitrogen and carbon stable isotopes in bone collagen and apatite of individuals from six precolonial Caribbean sites grouped into four subsistence categories: Hunter‐Fisher‐Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…There was also no apparent difference in fertility between the sites based on palaeodemographic estimates (Schurr & Powell, ). Similar results have since been obtained in a comparison of weaning times for archaeological populations from the Caribbean that included hunter‐gatherer‐fishers and several types of agriculturalists (Chinique de Armas and Pestle, ). They found no correlation between the start of weaning and the availability of cultigens.…”
Section: Discussionsupporting
confidence: 77%
“…There was also no apparent difference in fertility between the sites based on palaeodemographic estimates (Schurr & Powell, ). Similar results have since been obtained in a comparison of weaning times for archaeological populations from the Caribbean that included hunter‐gatherer‐fishers and several types of agriculturalists (Chinique de Armas and Pestle, ). They found no correlation between the start of weaning and the availability of cultigens.…”
Section: Discussionsupporting
confidence: 77%
“… t 1 and t 2 ages in a global comparison of previous WARN studies (Chinique de Armas & Pestle, ; King, Millard, et al, ; Smith et al, ; Tsutaya & Yoneda, ) Global average with ±1 SD shown…”
Section: Discussionmentioning
confidence: 96%
“…Compiling those studies that have used WARN to calculate weaning and complete weaning times (Chinique de Armas & Pestle, ; King et al, ; Smith, Pestle, Clarot, & Gallardo, ; Tsutaya, ), t 1 MDE averages 1.1 ± 0.8 and t 2 MDE averages 3.0 ± 1.3. This places this study's t 1 results earlier than most other sites and the t 2 values around the global average (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Outputs of the WARN model simulation includes maximum density estimators and posterior probabilities for: the start of weaning (t 1 , the age at which food other than mother’s milk is first added to the infant’s diet), the end of weaning (t 2 , when breast milk is no longer provided), as well as the δ 15 N value (δ 15 N wnfood ) of weaning foods, and E, the nitrogen isotope enrichment between mother and child [ 24 ]. Bayesian modeling approaches [ 79 ] are being increasingly used for dietary reconstructions [ 47 ], including BWPs [ 8 , 9 , 22 , 24 ]. They offer advantages over ad hoc explanations since conclusions are based on probabilities rather than the use of fixed offsets to account for the difference in δ 15 N between bone collagen and diet.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies of BWPs in Caribbean populations combined the analysis of δ 15 N and δ 13 C values in bone collagen with the use of Bayesian models to reconstruct the timing of weaning and the type of foods used during their weaning process [ 8 , 9 ]. The age at the start of weaning was found to be significantly later than observed in ethnographic populations from the area [ 43 – 45 ], or the age established by modern medical recommendations [ 46 ], an issue that had previously been observed when analyzing archaeological metadata more broadly [ 24 ].…”
Section: Introductionmentioning
confidence: 99%